0902 Sleep-Disordered Breathing in Interstitial Lung Disease Patients Referred for Lung Transplantation. (27th April 2018) - Rosenthal, M; Wong, J; Jyothula, S; Castriotta, R J
Abstract: Introduction: Over 2, 000 lung transplants (LTx) are done per year in the USA with the most frequent indication being interstitial lung disease (ILD). Sleep-disordered breathing (SDB) may be an under-appreciated risk in these patients. Methods: Polysomnography (PSG) of all patients with ILD referred for lung transplant evaluation over the past 2 years were reviewed. PSGs were scored according to AASM version 2 criteria and the 3 rd edition of the International Classification of Sleep Disorders. Results: There were 14 patients, aged 67.4 ± 7.2 [SD] years, 8 men and 6 women with 7 African-American, 6 Caucasian and 1 Hispanic. Six had idiopathic pulmonary fibrosis (IPF), 5 had other usual interstitial pneumonia (UIP) with specific etiology, 1 silicosis, 1 sarcoidosis and 1 interstitial lung disease - not otherwise specified (ILD-NOS). The mean forced vital capacity was 2.1 ± 0.8L, total lung capacity = 4.0 ± 1.7L with mean diffusing capacity = 39.9 ± 0.1% of predicted. Thirteen patients (93%) had obstructive sleep apnea (mean total respiratory disturbance index (tRDI) = 38.4 ± 35.2 obstructive respiratory events per hour of sleep). Two patients had central sleep apnea, 1 with sarcoidosis and 1 with ILD-NOS. The mean sleep efficiency was 59.5 ± 0.2%, baseline O2 saturation = 93.9 ± 0.02%, and an O2 nadir of 80.8 ± 0.1%. Five patients (36%) had sustained sleep-related hypoxemia requiring supplemental O2 . Four patients had sleep capnometry with a mean baseline awake end-tidal pCO2 = 32.3 ± 1.5 torr and a mean maximum sleep pCO2 = 41.9 ± 8.4 torr. Conclusion: Patients with ILD referred for lung transplantation are at high risk for obstructive sleep apnea, sleep-related hypoxemia and poor sleep efficiency. PSG may be recommended as part of the pre-LTx evaluation. Support (If Any): none.